Pemberdayaan Ibu PKK Melalui Pelatihan Pengolahan Limbah Ikan Menjadi Pelet Berprotein Tinggi di Desa Bulumeduro Tuban - Dian Nur Faizah; Muhamad Azwar Annas; Maida Nanda Widiatiningsih; Bagus Dwi Jauhari; Abelia Arianingsih Agistina (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
This community service program aims to improve the life skills of PKK mothers in Bulumeduro Village to be more productive through training in processing fish waste into high protein pellets and to reduce fish waste that is not properly utilized in order to create a better environmental ecosystem in Bulumeduro Village. The implementation methods used include extension or lecture method, carried out using direct practice or training methods, and assistance or monitoring for program sustainability. The results of community service activities using these three methods are that PKK mothers have a good understanding of how to process fish waste and how to make pellets and PKK mothers also know the benefits of processing fish waste into pellets, this can be seen from the pre-test and post-test results which show that there was an increase in PKK mothers' knowledge after counseling and training. The conclusion from the results of implementing the community service program is that PKK mothers become more productive in increasing income and improving life skills, in addition to increasing insight or knowledge regarding processing fish waste into high protein pellets.